Interaction of Polyaniline with Surface of Carbon Steel - Maria P. Sokolova; Michael A. Smirnov; Igor A. Kasatkin; Ivan Yu. Dmitriev; Natalia N. Saprykina; Alexander M. Toikka; Erkki Lahderanta; Galina K. Elyashevich (International Journal of Polymer Science)
The structure and barrier properties of the oxyhydroxide layers on a carbon steel surface covered with electroactive polyaniline were investigated. Two types of polymer structure differing in degree of macromolecular order were prepared by simultaneous (fast polymerization) or dropwise (slow polymerization) mixing of reagents. A larger amount of the most stable FeOOH modification was formed on steel covered with slowly polymerized sample during treatment in the corrosion-active medium. Amorphous rust products with weak barrier properties were observed in the sample prepared by fast polymerization. Additionally, barrier activity of dedoped polyaniline was studied with SEM, WAXD, and electrochemical methods.